Husserl lettore di Fichte: un’introduzione all’interpretazione fenomenologica del pensiero fichtiano tra teleologia, filosofia pratica e sistema trascendentale (Lebenswelt. Aesthetics and philosophy of experience., 2025)
In this paper, I aim to provide a historical-philosophical introduction as a preliminary step towards a comparison between Husserl’s and Fichte’s thought. In doing so, I aim to provide the foundations for a response to the absence of a systematic work that comprehensively addresses the comparison between the philosophy of Fichte and Husserl. My primary focus will be Husserl’s explicit references to Fichtean philosophy. First, I will briefly reconstruct the historical and intellectual context in which Husserl engaged with Fichte’s thought. I will then examine the lectures Husserl delivered at the University of Freiburg im Breisgau during the academic years 1917–1918. Finally, I will analyse various passages from Husserl’s corpus in which he directly addresses Fichte’s philosophy. By the end, it should be evident that Husserl attributes particular significance to Fichte’s teleological framework, the concept of practical philosophy, and the transcendental dimension of Fichte’s theoretical system.